To determine the correct function notation for the recursively defined sequence given by \( a_1 = -3 \) and \( a_n = a_{n-1} + 4 \), let’s analyze the options.
The recursive relationship indicates:
- The base case is \( a_1 = -3 \).
- Each subsequent term \( a_n \) is obtained by adding 4 to the previous term \( a_{n-1} \).
In function notation, we can express the sequence similarly. The relationship would be:
- \( f(1) = -3 \) which corresponds to the base case.
- The recursive formula can be written as \( f(n) = f(n-1) + 4 \) for \( n > 1 \), where \( f(n) \) defines the same relationship.
Now, looking at the options provided, we can identify the valid one based on this reasoning:
- The correct response would be: \( f(1) = -3; , f(n) = f(n-1) + 4 \)
This represents the base case and the recursive step accurately.